2001
DOI: 10.1016/s1010-7940(01)00760-6
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and mortality of acute lung injury and acute respiratory distress syndrome after pulmonary resection for bronchogenic carcinoma

Abstract: (1) ALI/ARDS is a severe complication following resection for primary bronchogenic carcinoma. (2) We did not detect any significant difference between the ALI/ARDS group and the control group regarding age, pre-operative lung function, staging and pre-operative radiotherapy. (3) ALI/ARDS is associated with high mortality, the highest mortality rates having been observed following right pneumonectomy and extended operation; it currently represents our leading cause of death following pulmonary resection for lun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
69
1
2

Year Published

2009
2009
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(75 citation statements)
references
References 23 publications
3
69
1
2
Order By: Relevance
“…Kutlu et al (1) investigated the frequency and mortality of acute lung injury and acute respiratory distress syndrome in patients after pulmonary resection, and reported that 45 (3.9%) of 1,139 resected cases had postoperative acute lung injury or acute respiratory distress syndrome, while 29 (64.4%) of these 45 patients died. Ruffini et al (2) reported that 27 (2.2%) of 1,221 cases had postoperative acute lung injury or acute respiratory distress syndrome, and that 14 (51.9%) of those 27 patients died. Muraoka et al (7) reported that 9 (56.3%) of 16 patients died due to respiratory failure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kutlu et al (1) investigated the frequency and mortality of acute lung injury and acute respiratory distress syndrome in patients after pulmonary resection, and reported that 45 (3.9%) of 1,139 resected cases had postoperative acute lung injury or acute respiratory distress syndrome, while 29 (64.4%) of these 45 patients died. Ruffini et al (2) reported that 27 (2.2%) of 1,221 cases had postoperative acute lung injury or acute respiratory distress syndrome, and that 14 (51.9%) of those 27 patients died. Muraoka et al (7) reported that 9 (56.3%) of 16 patients died due to respiratory failure.…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative interstitial pneumonia is a life-threatening complication with a high rate of mortality following surgery (1)(2)(3). Since it is difficult for patients with interstitial lung disease to undergo chemotherapy, radiation therapy or both, for their lung cancers, due to a high rate of exacerbation of interstitial pneumonia after treatment, surgical resection is sometimes the sole method of treatment for these patients.…”
Section: Introductionmentioning
confidence: 99%
“…While the incidence of lung injury after lung resection is fairly consistent, between 2 and 4 % [10][11][12], the mortality rate has decreased from almost 100 % to less than 40 %, largely due to improvements in ICU management [1].…”
Section: Epidemiology and Impact Of Ards After Lung Resection Surgerymentioning
confidence: 99%
“…The postoperative 30-day mortality rate for lung cancer patients is reportedly 0.4 -0.6% in Japan (Watanabe et al 2004;Sakata et al 2010), but lung resection occasionally leads to postoperative acute lung injury or acute respiratory distress syndrome (ALI/ARDS), including acute exacerbation of pulmonary fibrosis (Ruffini et al 2001;Dulu et al 2006;Alam et al 2007;Chida et al 2008;Tang et al 2008;Saito et al 2011). The American College of Chest Physicians (ACCP) evidence-based clinical practice guideline (Colice et al 2007) indicates the patients at increased risk for postoperative mortality or morbidity after lung cancer resection based on physiological evaluation.…”
mentioning
confidence: 99%
“…However, it does not identify a specific patient who is going to develop postoperative ALI/ARDS. Previous studies have suggested that age, extensive resection, poor respiratory function, excessive perioperative transfusion, and low predicted postoperative diffusion capacity are risk factors for postoperative ALI/ ARDS (Ruffini et al 2001;Dulu et al 2006;Alam et al 2007;Tang et al 2008). Recently, Japanese researchers reported that acute exacerbation of idiopathic pulmonary fibrosis, one of the postoperative ALI/ARDS, was associated with a preoperative subclinical fibrotic change (Chida et al 2008;Saito et al 2011).…”
mentioning
confidence: 99%